2018
DOI: 10.1186/s12864-018-4520-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-tissue transcriptomic study reveals the main role of liver in the chicken adaptive response to a switch in dietary energy source through the transcriptional regulation of lipogenesis

Abstract: BackgroundBecause the cost of cereals is unstable and represents a large part of production charges for meat-type chicken, there is an urge to formulate alternative diets from more cost-effective feedstuff. We have recently shown that meat-type chicken source is prone to adapt to dietary starch substitution with fat and fiber. The aim of this study was to better understand the molecular mechanisms of this adaptation to changes in dietary energy sources through the fine characterization of transcriptomic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 106 publications
6
41
0
Order By: Relevance
“…Sterol regulatory element (SREBPs) transcription factor regulate the expression of lipogenic genes, such as fatty acid synthase and acetyl-CoA carboxylase, involved in lipid biosynthesis and uptake [19] . Studies have shown that increased expression of SREBP-1C accelerate TG accumulation in diabetic rats [20]. We observed an upregulation in the mRNA expression of SREBP-1C in the hepatic and adipose tissue of diabetic rats.…”
Section: Discussionsupporting
confidence: 53%
“…Sterol regulatory element (SREBPs) transcription factor regulate the expression of lipogenic genes, such as fatty acid synthase and acetyl-CoA carboxylase, involved in lipid biosynthesis and uptake [19] . Studies have shown that increased expression of SREBP-1C accelerate TG accumulation in diabetic rats [20]. We observed an upregulation in the mRNA expression of SREBP-1C in the hepatic and adipose tissue of diabetic rats.…”
Section: Discussionsupporting
confidence: 53%
“…While we have focused solely on the liver in this study, our expectation is that the liver represents the bulk of the transcriptomic changes experienced under nutritional challenges. It has been previously shown that different diets lead to changed expression patterns in the liver, but not in muscle or adipose tissue (14). Most of the genes whose expression levels were altered by different diet composition (high vs low fat) in that study appear in Clusters 3 and 4 in the current study, with only two appearing in Cluster 2 (CPT1A, LPIN1).…”
Section: Discussionsupporting
confidence: 49%
“…Birds fed according to the CR and IF feeding regimens showed similar growth rates, although IF-fed birds had a consistently higher feed intake as previously reported (13). It is well known that the liver is central to the primary metabolic response to dietary changes in chickens (14), and shows large fluctuations in mass, glycogen content and lipid content under IF conditions in both RJF (13) and broiler breeders (10,15). Concomitant with these overt physiological effects are large effects on hepatic transcription.…”
Section: Introductionsupporting
confidence: 63%
“…The expression of genes involved in lipogenesis is tightly controlled by tissue-specific transcription factors [46]. CEBPA is among the well-known transcription factors involved in lipogenesis and adipogenesis and its activation is usually followed by increased fat deposition [47,48].…”
Section: Expression Regulation Of Genes Involved In Lipogenesismentioning
confidence: 99%